Płodność działalności planowanej - Michael E. Bratman (Ethics in Progress, 2013)
As normal adult human agents we have a remarkable trio of capacities. First, we are capable of acting over time in ways that involve important forms of intentional cross-temporal organization and coordination. Second, we are capable of acting together with others in ways that go significantly beyond standard forms of strategic interaction. Third, we are capable of self-governance. A theory of human agency should include an understanding of these capacities for temporally extended, for shared, and for self-governed intentional agency. In each case we have interrelated concerns that are conceptual, metaphysical, and normative. The response to these concerns is to seek to understand these three capacities as grounded in a common, core capacity for planning agency. This is the conjecture of the fecundity of planning agency.